90.9k views
5 votes
A. Given ????=P(1+????t),
i. Solve for P.
ii. Solve for ????.

1 Answer

6 votes

Answer:

i)
P=(A)/((1+r)^t)

ii)
r=1-((A)/(P))^{(1)/(t)}

Explanation:

Given:
A=P(1+r)^t

(i) solve for P for above formula. We have to isolate P from formula.


A=P(1+r)^t

Divide both side by
(1+r)^t


(A)/((1+r)^t)=(P(1+r)^t)/((1+r)^t)


P=(A)/((1+r)^t)

(ii) solve for r. We have to isolate r from formula.

Taking log both sides


\log A=\log (P(1+r)^t)


\log A=\log P+\log (1+r)^t
\because \log ab = \log a+\log b


\log A-\log P=t\log (1+r)
\because \log a^m=m\log a


(1)/(t)(\log A-\log P)=\log (1+r)


(1)/(t)(\log ((A)/(P)))=\log (1+r)
\because \log a-\log b=\log (a)/(b)


\log ((A)/(P))^{(1)/(t)}=\log (1+r)


1+r=((A)/(P))^{(1)/(t)}


r=1-((A)/(P))^{(1)/(t)}

User Golak Sarangi
by
4.5k points